Etika Menuntut Ilmu Dalam Kitab Ta’lim Muta’alim - Yusup Ruswandi; Wiyono Wiyono (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2020)
As a religion, Islam was regulated every asfects of life including how a good learning ethic is, this can be found in the books written by Islamic scholars. Among the books dealing with the learning ethics are ‘Ta’lim almuta’alim’ written by Syaikh Burhanudin Az-Zarnuji. The study of this book has been done with the part on determines the subjek that will be studied, selecting teachers and making friends, the purpose of this study is to analyze about determines the subjek that will be studied, selecting teachers and making friends according to Syaik Burhanudin Az-Zarnuji. Research Methods are conducted with literature study research through a qualitative approach. Research show according to Syaik Burhanudin Az-Zarnuji that the most important knowledge is the Tawheed, and the next step is shariah, then after that the others. Thereafter a student should select a teacher who is knowledgeable, religiously and morally. Than in choosing friends should choose good friends who can motivate the spirit of learning.